Influence of Self-Efficacy Competences on Management of Scholarly Information among Postgraduate Students in Kiambu County Kenya - Njiru, Leah; Thinguri, Ruth; Chui, Mary (African Journal of Education and Practice, 2023)
Purpose: The study investigates the effects of student literacy self-efficacy competences on management of scholarly information among postgraduate students in Kiambu county Kenya. Self-efficacy is a tool in information literacy. Methodology: The study adopted a mixed methodology so as to collect and analyze qualitative and quantitative data where data was collected using self-administered questionnaires. Findings: The findings of the study revealed that self-efficacy as a practice of information literacy influence Management of Scholarly Information. Unique Contribution to Theory, Practice and Policy: The paper recommends that more attention be given to the practice of self-efficacy competence since it's a vital factor evaluate to quality papers among scholars. Further studies should evaluate the extent to which self-efficacy influence postgraduate scholars on their scholarly information management.